Appropriate technology for sustainable food security - Pinstrup-Andersen, Per (International Food Policy Research Institute, 2001)
Modern science and technology offer tremendous opportunities for improving the well-being of current and future generations and the environment. However, they also embody risks. Science and technology must be guided toward outcomes desired by society. Guiding science and technology to benefit the poor and food insecure in developing countries is the focus of this set of policy briefs.